Seminars in Dysphagia - Speyer, Renee; Bogaardt, Hans (IntechOpen, 2015)
Seminars in Dysphagia provides a comprehensive overview of contemporary issues in the field of dysphagia assessment, treatment and management in diverse subject populations. Expert views are shared by international clinical experts from different medical and allied health fields. This book contains an introductory chapter on the anatomical structures and physiology processes that underpin dysphagia and discusses the effects of polypharmacy and ageing on deglutition. Contemporary practices of functional assessment of swallowing and the endoscopic assessment for both oropharyngeal and esophageal dysphagia are reviewed. Both the nutritional support and decision making in oral route are described and the impact of dysphagia on carers and family when managing dysphagia. Several chapters are dedicated to outlining the manifestation and consequences of dysphagia in specific populations, including persons with Parkinsons disease, dystonia, chronic obstructive pulmonary disease and mixed connective tissue disease.